THE EFFECT OF THE YEAR ON THE STEPPE PEONY'S MORPHOLOGICAL AND ORNAMENTAL TRAITS - Prijić, Željana; Marković, Tatjana; Radanović, Dragoja; Xue , Jingqi; Zhang, Xiuxin; Gordanić, Stefan; Mikić, Sara; Dragumilo, Ana; Čutović, Natalija; Batinic, Petar (Acta herbologica, 2023)
The steppe peony (Paeonia tenuifolia L.) is an endangered medicinal plant species that occurs in Serbia in three habitats, of which the Deliblato Sands are the richest. Based on the results of research conducted at Deliblato Sands in 2023, it was found that the development of the flowering stems of Paeonia tenuifolia was not affected by the slightly higher average winter temperatures. 100 randomly selected plants were measured in the field, including height, plant girth, number of branches per plant bush, the ratio of flowering to non-flowering branches, shoot-to-root ratio, and stem-to-branch-to-flower ratio. The results showed that the root-to-shoot ratio was 1:2,5, the average height of the tested plants was 41±6 cm, ranging from 30-60 cm, and the girth of the plant bush was 121±30 cm, ranging from 40-170 cm, and was positively correlated with the number of branches. The average number of branches per plant was 8±2,5. Based on the measurement of absolute dry plant material, it was found that the mass of a branch contained on average 22.5% of the stem, 73.5% of the leaf twigs, and 4% of the flower mass. The petals make up, on average, 34.3% of the mass of the flower.
Keywords: Paeonia tenuifolia L., shoot: root ratio, temperature, humidity, Deliblato Sands, medicinal and ornamental species